Optimising a curriculum for clinical haematology and biochemistry in sports medicine: a Delphi approach - Fallon, K E; Trevitt, A C (British journal of sports medicine, 2006)
Objectives: To investigate issues of curriculum in the context of a postgraduate sports medicine training programme, specifically in the field of clinical biochemistry and haematology. Methods: Following the Delphi methodology, a series of sequential questionnaires was administered to curriculum developers, clinical teachers, examiners, and registrars. Results: Agreement on a core syllabus for this subject with an indication of the core aims and objectives of teaching and learning in this field and the associated required skills and competencies. An indication of current and ideal teaching and learning methods and reasons for these preferences. A consensus of key features of a teaching module for this field and of appropriate methods of examination. Conclusions: The data derived from this study, as well as the experience of engaging in it, will better inform curriculum developers, teachers, and students of one another’s perceptions as to what is important in and appropriate to teaching and learning in this field of sports medicine. Engagement in the exercise and broader consideration of the outcomes by those who develop the curriculum, teach, and formulate the examination process will facilitate attainment of the ideal of well aligned teaching, learning, and examination in this specific field.